Open Price Contract Compertive Study: Comparative Study - حسن حيدر فليح (Journal of Legal Sciences, 2019)
The ultimate goal of any sale contract is to maximize the combined returns of the parties, knowing that these returns are not realized (in long-term contracts) except in the final stages of the contract. Therefore, this requires the parties to the contract to leave some elements open, including the price, because the adoption of a fixed price and inflexible will not be appropriate to meet their desires when contracting, especially with ignorance of matters beyond their will and may affect the market conditions, and the possibility of modifying the fixed price through The elimination is very limited, especially when the parties to the contract are equally in terms of economic strength. Hence, in order to respond to market uncertainties, the parties have been allowed to combine the fixed and open conditions of the contract. They are accurate, allowing flexible conditions to cope with unexpected market fluctuations. In this combination of conditions, the seller and the buyer leave a set of elements in the contract open, for example (price, time, quantity) to maintain the functional nature of the business.